Guilty Feelings, Targeted Actions - Cryder, Cynthia E. (Pers Soc Psychol Bull, 2012)
Early investigations of guilt cast it as an emotion that prompts broad reparative behaviors that help guilty individuals feel better about themselves or about their transgressions. The current investigation found support for a more recent representation of guilt as an emotion designed to identify and correct specific social offenses. Across five experiments, guilt influenced behavior in a targeted and strategic way. Guilt prompted participants to share resources more generously with others, but only did so when those others were persons whom the participant had wronged and only when those wronged individuals could notice the gesture. Rather than trigger broad reparative behaviors that remediate one’s general reputation or self-perception, guilt triggers targeted behaviors intended to remediate specific social transgressions.